A Systematic Review of the Efficacy of Bioactive Compounds in Cardiovascular Disease: Phenolic Compounds - Rangel-Huerta, Oscar D. (Nutrients, 2015)
The prevalence of cardiovascular diseases (CVD) is rising and is the prime cause of death in all developed countries. Bioactive compounds (BAC) can have a role in CVD prevention and treatment. The aim of this work was to examine the scientific evidence supporting phenolic BAC efficacy in CVD prevention and treatment by a systematic review. Databases utilized were Medline, LILACS and EMBASE, and all randomized controlled trials (RCTs) with prospective, parallel or crossover designs in humans in which the effects of BAC were compared with that of placebo/control were included. Vascular homeostasis, blood pressure, endothelial function, oxidative stress and inflammatory biomarkers were considered as primary outcomes. Cohort, ecological or case-control studies were not included. We selected 72 articles and verified their quality based on the Scottish Intercollegiate Guidelines Network, establishing diverse quality levels of scientific evidence according to two features: the design and bias risk of a study. Moreover, a grade of recommendation was included, depending on evidence strength of antecedents. Evidence shows that certain polyphenols, such as flavonols can be helpful in decreasing CVD risk factors. However, further rigorous evidence is necessary to support the BAC effect on CVD prevention and treatment.